Electrolyte and lithium ion battery using same
By using the combination of additives A and B of specific structures in the lithium-ion battery electrolyte, the problem of electrolyte decomposition at high voltage is solved, forming a stable membrane structure, reducing side reactions, and removing harmful substances, achieving high efficiency stability and long life of lithium-ion batteries.
Patent Information
- Application Number
- CN202411999661.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-12-31
AI Technical Summary
Existing lithium-ion battery electrolytes are prone to oxidation and decomposition at high voltages, resulting in reduced performance. High lithium salt concentration will bring high cost and low safety. The new solvent system has problems such as lower low temperature performance and poor negative electrode compatibility.
The combination of additive A and additive B is adopted. The general structural formula of additive A is wherein at least one of R1, R2, and R3 is an alkyl group, and the general structural formula of additive B is an alkyl group wherein R4 is C1 to C4. These additives can inhibit the decomposition of the electrolyte under high temperature conditions, and form stable CEI films and SEI films on the surface of the positive and negative electrodes, reduce side reactions, and remove harmful substances produced in the electrolyte through complexation.
It effectively improves the high-voltage application performance of lithium-ion batteries, extends the service life of the battery, improves the circulation and high-temperature performance, and reduces the side reaction between the electrolyte and the positive and negative electrodes.
Smart Images

Figure CN119764559A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of lithium ion batteries, and in particular, relates to an electrolyte and a lithium ion battery using the electrolyte. Background Art
[0002] As pure electric vehicles, hybrid vehicles and portable energy storage devices continue to increase the energy density of lithium-ion batteries, people are looking forward to developing lithium-ion batteries with higher energy density and power density to achieve long-term endurance and energy storage of electric devices. High operating voltage is one of the methods to increase the energy density of lithium-ion batteries. Under high operating voltage, the electrolyte needs to have good oxidation resistance and a stable electrochemical window to ensure that lithium-ion batteries can maintain stable circulation under high voltage.
[0003] However, commercial lithium-ion battery electrolytes are generally composed of carbonate organic solvents and lithium hexafluorophosphate (LiPF6). Carbonate solvents are mainly composed of chain carbonates such as dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), and cyclic carbonates such as propylene carbonate (PC) and ethylene carbonate (EC). However, the above organic solvents have low oxidation potentials and are prone to oxidative decomposition under high voltages and are difficult to exist stably, resulting in reduced performance of lithium-ion batteries containing these solvents in the electrolyte.
[0004] The voltage resistance of commercial electrolytes can usually be improved by:
[0005] (1) Increasing the lithium salt concentration in the electrolyte containing carbonate solvents increases the number of complexes between lithium ions and solvent molecules, which enhances the antioxidant properties of the complexed solvent molecules and the stability of the electrolyte. In addition, compared with traditional electrolytes, high-concentration electrolytes have enhanced flame retardancy and improved battery safety.
[0006] (2) Use new high-voltage electrolyte solvents to replace carbonate solvents. The new solvents include sulfones, nitriles, ionic liquids and fluorinated electrolytes. These new system electrolytes can meet the high voltage requirements to a certain extent.
[0007] (3) By adding high-voltage electrolyte additives to traditional carbonate electrolytes, the additives can preferentially decompose on the positive electrode surface to form a CEI film during battery cycling, which can protect the integrity of the high-voltage electrode material to a certain extent and reduce the side reactions caused by the contact between the high-voltage positive electrode and the electrolyte.
[0008] Although the above methods can improve the high voltage resistance of the electrolyte to a certain extent, they all have certain limitations. High lithium salt concentration will lead to high cost and low safety of the electrolyte. Sulfone solvents and ionic liquids have relatively high melting points, which reduces their performance at low temperatures. The poor compatibility of nitrile with graphite negative electrodes also limits the practical application of new solvent system electrolytes. In comparison, high-voltage multifunctional additives can simply and effectively improve the high voltage resistance of the electrolyte. However, the high-voltage electrolyte additives currently available on the market all have a single positive electrode film-forming function and are relatively few in number. Therefore, the development of new practical multifunctional high-voltage electrolyte additives is still an urgent problem to be solved. Summary of the invention
[0009] The present invention provides an electrolyte and a lithium ion battery using the same. The electrolyte has good stability and can form a CEI film and a SEI film with excellent performance on the positive electrode and the negative electrode of the lithium ion battery, respectively, thereby effectively reducing the probability of decomposition of the electrolyte under high-voltage application conditions and effectively improving the high-voltage application performance of the lithium ion battery.
[0010] According to a first aspect of the present invention, an electrolyte is provided, characterized in that: it comprises an additive A and an additive B; the general structural formula of the additive A is Wherein, at least one of R1, R2 and R3 is an alkeneoxy group; the general structural formula of additive B is Wherein, R4 is a C1-C4 alkyl group.
[0011] In the electrolyte provided by the present invention, additive A and additive B are used to effectively improve the stability of the electrolyte. On the one hand, the addition of the two additives inhibits the decomposition of the electrolyte under high temperature conditions. On the other hand, the two additives are easily oxidized and reduced to form a CEI film and SEI film with stable structure on the surface of the positive and negative electrodes, thereby effectively reducing the side reactions between the electrolyte and the positive and negative electrodes. Additive A and additive B both contain nitrogen atoms. The nitrogen atoms with lone pairs of electrons can play a complexing role on the transition metal ions dissolved from the positive electrode active material, avoiding the migration of transition metal ions to the negative electrode and destroying the negative electrode SEI film. In addition, the combination of additive A and additive B can effectively remove PF5, HF, CO2 and H2O generated in the electrolyte during the operation of the lithium ion battery, effectively reducing the risk of corrosion of the internal parts of the battery by the above materials, improving the cycle performance of the lithium ion battery, and extending the service life of the lithium ion battery.
[0012] Preferably, the additive A is selected from (CAS101-37-1), (CAS 87024-56-4), (CAS 50729-70-9), (CAS 30358-11-3), (CAS 3922-50-7), At least one of (CAS16715-84-7).
[0013] Preferably, additive A is Selecting a material having the above molecular structure as additive A can enhance the complexation of transition metal ions dissolved from the positive electrode, further inhibit the damage of the transition metal ions in the electrolyte to the negative electrode SEI film, and the above material can further improve the removal effect of HF in the electrolyte.
[0014] Preferably, the additive B is selected from (CAS 81606-79-3), (CAS91040-87-8), (CAS1248902-14-8,), At least one of (CAS1490391-62-2).
[0015] Preferably, the general structural formula of additive B is Wherein, R5 and R6 are independently selected from hydrogen, C1-C10 straight chain or branched alkyl or alkoxy, C1-C10 halogenated or unsubstituted straight chain or branched alkyl or alkoxy. Using the material with the above molecular structure as additive B can further improve the removal effect of HF in the electrolyte.
[0016] Preferably, the molar mass of additive A is 190-300, the molar mass of additive B is 100-180, and in the electrolyte, the mass ratio of additive A to additive B satisfies the mass of additive A: the mass of additive B = 0.5-0.8: 1. In this solution, by optimizing the ratio of additive A to additive B, the stability of the positive electrode CEI film and the negative electrode SEI film of the lithium ion battery is taken into account, and the working stability of the lithium ion battery is improved.
[0017] Preferably, the sum of the masses of additive A and additive B accounts for 0.6 wt.% to 2 wt.% of the mass of the electrolyte.
[0018] Preferably, the electrolyte further includes at least one of a sulfur-containing additive, a carbonate additive, and a lithium salt additive; the sulfur-containing additive includes at least one of vinyl sulfate (DTD), 1,3-propane sultone (PS), and 1,3-propylene sultone (PST); the carbonate additive includes vinylene carbonate (VC); the lithium salt additive includes at least one of lithium bis(fluorosulfonyl)imide (LiFSI), lithium difluorophosphate (LiPO2F2), lithium dioxalatoborate (LiBOB), and lithium difluorodioxalatophosphate (LiODFP).
[0019] Preferably, the sulfur-containing additive includes PST, and in the electrolyte, the mass of additive A: 1,3-propene sultone = 0.3-1: 0.5-2. Based on the use of additive A and additive B in the electrolyte, and further using PST as the sulfur-containing additive in the electrolyte formula, the high temperature performance of the lithium-ion battery can be effectively improved.
[0020] Preferably, the electrolyte includes an organic solvent component, the mass of the organic solvent component accounts for 80wt.% to 90wt.% of the mass percentage of the electrolyte, and the organic solvent component includes cyclic carbonate, chain carbonate and chain carboxylic acid ester, and the mass ratio is calculated as follows: cyclic carbonate: chain carbonate: chain carboxylic acid ester = 10 to 25: 50 to 80: 5 to 20. In the above scheme, by selecting the components of the organic solution suitable for additive A and additive B and regulating the proportion, the high temperature cycle characteristics of the lithium ion battery can be further improved.
[0021] Preferably, the cyclic carbonate includes fluoroethylene carbonate (FEC), the chain carbonate includes diethyl carbonate, and the chain carboxylic acid ester includes ethyl difluoroacetate.
[0022] Preferably, in the electrolyte, the mass of fluoroethylene carbonate: the mass of ethylene carbonate: the mass of diethyl carbonate: the mass of ethyl difluoroacetate = 5-15: 5-15: 60-80: 10-20.
[0023] According to a second aspect of the present invention, there is provided a lithium ion battery comprising the electrolyte as described above.
[0024] Specific embodiment
[0025] In order to enable those skilled in the art to better understand the solutions of the present invention, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only embodiments of a part of the present invention, rather than all embodiments.
[0026] Example 1
[0027] According to the mass percentage of the components, the electrolyte formula used in this embodiment is as follows: additive A 0.3%, additive B 0.4%, VC 0.2%, LiODFP 0.5%, PST 1%, lithium hexafluorophosphate (LiPF6) 15%, and the balance is an organic solvent component. Among them, the organic solvent component in the above electrolyte formula is composed of fluoroethylene carbonate, ethylene carbonate, and diethyl carbonate, wherein the mass fraction of fluoroethylene carbonate is 10%, the mass fraction of ethylene carbonate is 10%, the mass fraction of ethyl difluoroacetate is 15%, and the mass fraction of diethyl carbonate is 65%. Additive B in the above electrolyte formula is Different experimental groups were set up with additive A in the formula as a variable, and were marked as: experimental group 1-1, experimental group 1-2, experimental group 1-3, experimental group 1-4, and experimental group 1-5. The additive A used in each of the above experimental groups is shown in Table 1.
[0028] Table 1. Numbers of the experimental groups in this example and the additives A used accordingly
[0029]
[0030] Each experimental group prepared materials according to the electrolyte formula composition adopted by each experimental group. First, the materials used to prepare the organic solvent component were mixed evenly to obtain the organic solvent component. Then, at 10°C and in an argon atmosphere, the formulated amount of VC, PST, LiODFP, additive A, additive B, and LiPF6 were added to the organic solvent component. The temperature was maintained at 10°C, and the resulting mixture was fully stirred until the solid material was fully dissolved to obtain a uniform solution, thereby preparing the electrolyte.
[0031] Example 2
[0032] According to the mass percentage of the components, the electrolyte formula used in this embodiment is as follows: additive A 0.3%, additive B 0.4%, VC 0.2%, LiODFP 0.5%, PST 1%, lithium hexafluorophosphate (LiPF6) 15%, and the balance is an organic solvent component. Among them, the organic solvent component in the above electrolyte formula has the same component composition as the organic solvent component included in the electrolyte formula used in Example 1. The additive A in the above electrolyte formula is the triazine compound I in Table 1, and different experimental groups are set with the additive B in the formula as a variable, which are marked as experimental group 2-1 and experimental group 2-2 respectively. The additive B used in each of the above experimental groups is shown in Table 2. In addition, since the experimental group set in this embodiment and the experimental group 1-1 of Example 1 use the same type of additive A to prepare the electrolyte, the difference is also the additive B in the electrolyte formula, so the experimental group 1-1 of Example 1 is also loaded in Table 2 for comparison.
[0033] Table 2. Numbers of the experimental groups in this example and the corresponding additives B used
[0034]
[0035] Each experimental group prepared materials according to the electrolyte formula composition adopted by each experimental group. First, the materials used to prepare the organic solvent component were mixed evenly to obtain the organic solvent component. Then, at 10°C and in an argon atmosphere, the formulated amount of VC, PST, LiODFP, additive A, additive B, and LiPF6 were added to the organic solvent component. The temperature was maintained at 10°C, and the resulting mixture was fully stirred until the solid material was fully dissolved to obtain a uniform solution, thereby preparing the electrolyte.
[0036] Comparative Example 1
[0037] In this comparative example, control groups 1-1, 1-2 and 1-3 are set up to prepare electrolytes. The formulas and methods of preparing the electrolytes of the control groups are as follows.
[0038] Control group 1-1:
[0039] Taking the electrolyte formula used in the experimental group 1-1 of Example 1 as a reference, the electrolyte formula used in the control group 1 is different from that used in the experimental group 1-1 in that the additive A used is (hereinafter referred to as "triazine compound VI"), in the electrolyte formula used in control group 1, triazine compound VI is used to replace triazine compound I in the electrolyte formula of experimental group 1-1 in equal mass as additive A in the electrolyte formula. In addition, other materials in the electrolyte formula used in control group 1 are consistent with the materials and proportions used in the electrolyte formula of experimental group 1-1. Prepare the materials according to the electrolyte formula used in control group 1, and complete the preparation of the electrolyte according to the method used to prepare the electrolyte in experimental group 1-1.
[0040] Control group 1-2:
[0041] Taking the electrolyte formula used in the experimental group 2-1 of Example 2 as a reference, the electrolyte formula used in the control group 2 is different from that used in the experimental group 2-1 in that the additive B used is (hereinafter referred to as "triazole compound IV"), in the electrolyte formula used in control group 2, triazole compound IV is used to replace triazole compound I in the electrolyte formula of experimental group 2-1 in equal mass as additive B in the electrolyte formula, except that the other materials in the electrolyte formula used in control group 2 are consistent with the materials and proportions used in the electrolyte formula of experimental group 2-1. Prepare the materials according to the electrolyte formula used in control group 2, and complete the preparation of the electrolyte according to the method used to prepare the electrolyte in experimental group 2-1.
[0042] Control Groups 1-3:
[0043] According to the mass percentage of the components, the electrolyte formula used in the control group 6 is as follows: VC 0.2%, LiODFP 0.5%, PST 1%, LiPF6 15%, and the balance is the organic solvent component. In the above electrolyte formula, the organic solvent component used has the same component composition as the organic solvent component included in the electrolyte formula used in Example 1.
[0044] Prepare materials according to the electrolyte formula composition. First, mix the materials used to prepare the organic solvent component evenly to obtain the organic solvent component. Then, add the formulated amount of VC, PST, LiODFP, and LiPF6 to the organic solvent component at 10°C and in an argon atmosphere. Keep the temperature at 10°C, and fully stir the resulting mixture until the solid material is fully dissolved to obtain a uniform solution, thereby preparing the electrolyte.
[0045] Preparation Example 1
[0046] The electrolyte used to prepare the lithium-ion battery in this preparation example is the electrolyte prepared in Example 1, Example 2, and Comparative Example 1.
[0047] The method for preparing a lithium ion battery in this preparation example is as follows:
[0048] Graphite is used as the negative electrode active material, and graphite, conductive agent acetylene black, binder CMC, and SBR are prepared into a negative electrode slurry in a mass percentage of 94:1:2:3. The negative electrode slurry is coated on a copper foil current collector and vacuum dried to obtain a negative electrode plate. The ternary material NCM523 is used as the positive electrode active material, and NCM523, conductive agent acetylene black, and binder PVDF are prepared into a positive electrode slurry in a mass ratio of 94:3:3. The positive electrode slurry is coated on an aluminum foil current collector and vacuum dried to obtain a positive electrode plate. The electrolyte prepared in Example 1, Example 2, and the comparative example are respectively used to assemble a soft-pack battery with the above-mentioned positive electrode plate, the negative electrode plate, and a Celgard2400 separator.
[0049] Test Example 1
[0050] 1. Electrolyte HF content test
[0051] (1) Test object
[0052] The electrolyte prepared in Example 1, Example 2 and Comparative Example 1.
[0053] (2) Test method
[0054] The electrolyte was stored at 45°C, and the HF content in the electrolyte was tested by ice water titration at the start time of the experiment and after storage for 15 days, where the HF content measured at the start time of the experiment was recorded as HF-0d, and the HF content measured after storage for 15 days was recorded as HF-15d.
[0055] 2. Cycle performance test of lithium-ion batteries
[0056] (1) Test object
[0057] The lithium ion battery prepared in Preparation Example 1 was used as a test object.
[0058] (2) Test method
[0059] Normal temperature cycle test: Place the lithium-ion battery at 25°C, record the initial capacity, marked as A1, cycle the lithium-ion battery at 5C / 5C for 2000 cycles, and record the capacity of the lithium-ion battery in this state, marked as A2. The capacity retention rate of the lithium-ion battery cycled at room temperature for 2000 cycles is calculated as follows:
[0060] Normal temperature cycle capacity retention rate (%) = A2 / A1×100%.
[0061] High temperature cycle test: Place the lithium-ion battery at 45°C, record the initial capacity, marked as A3, cycle the lithium-ion battery at 5C / 5C for 2000 cycles, and record the capacity of the lithium-ion battery in this state, marked as A4. The capacity retention rate of the lithium-ion battery after 2000 cycles of high temperature cycling is calculated as follows:
[0062] High temperature cycle capacity retention rate (%) = A4 / A3×100%.
[0063] 3. High temperature storage performance test of lithium-ion batteries
[0064] (1) Test object
[0065] The lithium ion battery prepared in Preparation Example 1 was used as a test object.
[0066] (2) Test method
[0067] The lithium-ion battery was charged at a constant current of 1.0C (nominal capacity) to a voltage of 4.4V, then charged at a constant voltage of 4.4V to a current ≤0.05C, and after standing for 10 minutes, discharged at a constant current of 1C to 2.8V. The above is one charge and discharge cycle. The lithium-ion battery under test was charged and discharged 5 times at a charge and discharge rate of 1C at 25°C, and then charged to a fully charged state at a rate of 1C, and the capacity Q0 and battery volume V0 of the lithium-ion battery were recorded. The fully charged battery was stored at 60°C for 90 days, and the volume V1 and 1C discharge capacity Q1 of the lithium-ion battery were recorded. Then the lithium-ion battery was charged and discharged at a rate of 1C for 5 weeks at 25°C, and the 1C discharge capacity Q2 was recorded. The experimental data such as the battery's high-temperature storage capacity retention rate, capacity recovery rate, and volume change rate were calculated. The calculation formula used is as follows:
[0068] Capacity retention rate (%) = Q1 / Q0 × 100%;
[0069] Capacity recovery rate (%) = Q2 / Q0 × 100%;
[0070] Volume change rate (%) = (V1-V0) / V0×100%.
[0071] 4. Test Results
[0072] The test results of this test case are shown in Table 3.
[0073] The electrolytes prepared in the control groups 1-3 contain neither triazine compounds nor triazole compounds. From the test results, it can be seen that the electrolytes have significantly higher HF content in the electrolyte HF content test involved in this test example. Moreover, among all the lithium-ion batteries tested in this test example, the lithium-ion batteries using the electrolytes in the control groups 1-3 show obvious deficiencies in high-temperature storage performance and normal temperature / high temperature cycle performance.
[0074] Compared with the electrolyte provided by the control group 1-3, the electrolytes provided by the experimental groups 1-1, 1-2, 1-3, 1-4, 1-5, 2-1 and 2-2 respectively contained the general structural formula (wherein at least one of R1, R2, and R3 is an olefinic oxide) and the general structural formula is (wherein R4 is an alkyl group) of additive B. Based on the combination of the above additives A and additive B: first, the decomposition of the electrolyte under high temperature conditions is inhibited; second, the above two additives can easily form a structurally stable CEI film and SEI film on the surface of the positive and negative electrodes, thereby effectively reducing the side reactions between the electrolyte and the positive and negative electrodes; third, additives A and additive B inhibit the dissolution of transition metal ions from the positive electrode active material, thereby preventing the transition metal ions from migrating to the negative electrode and destroying the negative electrode SEI film; fourth, the combination of the above two additives can effectively remove PF5, HF, CO2 and H2O generated in the electrolyte during the operation of the lithium-ion battery. In summary, based on the combination of additives A and additive B, the high-temperature storage performance and cycle performance of lithium-ion batteries using these electrolytes can be improved to a certain extent.
[0075] The electrolytes prepared by the control group 1-1 and the control group 1-2 also contain triazine compounds and triazole compounds. However, compared with the product performance of the experimental group 1-1 electrolyte, the experimental group 1-2 electrolyte, the experimental group 1-3 electrolyte, the experimental group 1-4 electrolyte, the experimental group 1-5 electrolyte, the experimental group 2-1 electrolyte, the experimental group 2-2 electrolyte and the lithium ion batteries using these electrolytes, the product performance of the control group 1-1 electrolyte, the control group 1-2 electrolyte and the lithium ion batteries using these electrolytes still show obvious deficiencies. Among them, the triazine compound contained in the control group 1-1 electrolyte does not contain olefinic oxide, that is, the triazine compound used in the control group 1-1 to prepare the electrolyte does not belong to additive A, and the triazole compound contained in the control group 1-2 electrolyte does not contain cyano group, that is, the triazole compound used in the control group 1-2 to prepare the electrolyte does not belong to additive B. Therefore, although the electrolytes prepared in the control group 1-1 and the control group 1-2 respectively contain triazine compounds and triazole compounds, since the triazine compounds and triazole compounds used in the two electrolytes do not conform to the structural formulas of additives A and additives B at the same time, there is actually no combination of additives A and additives B in the above two electrolytes. The test results of this test example show that for electrolytes, not any combination of triazine compounds and triazole compounds can achieve the same effect as the combination of additives A and additives B.
[0076] In the electrolytes prepared by Experimental Group 1-1, Experimental Group 1-2, Experimental Group 1-3, Experimental Group 1-4, and Experimental Group 1-5, the difference in the formula composition lies in the specific type of additive A. Among the above electrolytes, the electrolyte provided by Experimental Group 1-1 measured the lowest HF content under the same test conditions in the electrolyte HF content test of this test example, and among the lithium-ion batteries using these electrolytes, the lithium-ion battery using the electrolyte of Experimental Group 1-1 can show the best high-temperature application performance and cycle performance in the test results of this test example. The additive A contained in the electrolyte of Experimental Group 1-1 is triazine compound I, whose structure is Based on the application of additive B, the use of triazine compound I as additive A can better complex the transition metal ions dissolved from the positive electrode of the lithium-ion battery, thereby preventing the transition metal ions from migrating to the negative electrode and destroying the SEI film.
[0077] In the electrolytes prepared by Experimental Group 1-1, Experimental Group 2-1, and Experimental Group 2-2, the difference in the formula composition lies in the specific type of additive B. The lithium-ion batteries using the above electrolytes can achieve excellent high-temperature application performance and excellent cycle performance. Among the above electrolytes, the electrolyte provided by Experimental Group 1-1 measured the lowest HF content under the same test conditions in the electrolyte HF content test of this test example.
[0078] Table 3. Test result statistics of test case 1
[0079]
[0080]
[0081] Comparative Example 2
[0082] As described above, the electrolytes provided by the experimental groups in Example 1 are all electrolytes using additives A and additives B in combination. Among these electrolytes, the electrolyte provided by experimental group 1-1 of Example 1 and the lithium ion battery using the electrolyte have achieved the best comprehensive performance among similar test objects in Test Example 1. Based on the test results in Test Example 1, this comparative example uses experimental group 1-1 of Example 1 as a control, and sets control groups 1-4 and 1-5 to prepare electrolytes. The formulas and methods of preparing the electrolytes of these two control groups are as follows.
[0083] Control Groups 1-4:
[0084] According to the mass percentage of the components, the electrolyte formula used in the control group 4 is as follows: additive A 0.7%, VC 0.2%, LiODFP 0.5%, PST 1%, LiPF6 15%, and the balance is the organic solvent component. In the above electrolyte formula, the organic solvent component used has the same component composition as the organic solvent component included in the electrolyte formula used in Example 1, and the additive A used is the same as the experimental group 1-1 of Example 1, both of which are triazine compound I.
[0085] Prepare materials according to the electrolyte formula composition. First, mix the materials used to prepare the organic solvent component evenly to obtain the organic solvent component. Then, add the formulated amount of VC, PST, LiODFP, additive A, and LiPF6 to the organic solvent component at 10°C and in an argon atmosphere. Keep the temperature at 10°C, and fully stir the resulting mixture until the solid material is fully dissolved to obtain a uniform solution, thereby preparing the electrolyte.
[0086] Control Groups 1-5:
[0087] According to the mass percentage of the components, the electrolyte formula used in the control group 5 is as follows: additive B 0.7%, VC 0.2%, LiODFP 0.5%, PST 1%, LiPF6 15%, and the balance is the organic solvent component. In the above electrolyte formula, the organic solvent component used has the same component composition as the organic solvent component included in the electrolyte formula used in Example 1, and the additive B used is the same as the experimental group 1-1 of Example 1, both of which are triazole compound I.
[0088] Prepare materials according to the electrolyte formula composition. First, mix the materials used to prepare the organic solvent component evenly to obtain the organic solvent component. Then, add the formulated amount of VC, PST, LiODFP, additive B, and LiPF6 to the organic solvent component at 10°C and in an argon atmosphere. Maintain the temperature at 10°C and fully stir the resulting mixture until the solid material is fully dissolved to obtain a uniform solution, thereby preparing the electrolyte.
[0089] Preparation Example 2
[0090] The electrolyte used to prepare the lithium-ion battery in this preparation example is the electrolyte prepared in Comparative Example 2.
[0091] The method for preparing the lithium ion battery in this preparation example is consistent with the method for preparing the lithium ion battery in Preparation Example 1.
[0092] Test Example 2
[0093] 1. Electrolyte HF content test
[0094] (1) Test object
[0095] The electrolyte prepared in Comparative Example 2 was used as the test object.
[0096] (2) Test method
[0097] The method for testing the HF content of the electrolyte in this test example is consistent with the method for testing the HF content of the electrolyte used in Test Example 1.
[0098] 2. Cycle performance test of lithium-ion batteries
[0099] (1) Test object
[0100] The lithium ion battery prepared in Preparation Example 2 was used as a test object.
[0101] (2) Test method
[0102] The method used in this test example to perform a cycle performance test on a lithium-ion battery is consistent with the cycle performance test method of a lithium-ion battery used in Test Example 1.
[0103] 3. High temperature storage performance test of lithium-ion batteries
[0104] (1) Test object
[0105] The lithium ion battery prepared in Preparation Example 2 was used as a test object.
[0106] (2) Test method
[0107] The method used in this test example to test the high temperature storage performance of lithium-ion batteries is consistent with the high temperature storage performance test method of lithium-ion batteries used in Test Example 1.
[0108] 3. Test results
[0109] The test results of this test example are shown in Table 4. For the sake of comparison, Table 4 also shows the test results of the electrolyte of Experimental Group 1-1 of Example 1 and the lithium ion battery prepared using the electrolyte in Test Example 1. In the two control groups set in Comparative Example 2, the electrolyte of Control Group 1-4 contains the same type of additive A as the electrolyte of Experimental Group 1-1, but the electrolyte of Control Group 1-4 does not contain additive B, and the electrolyte of Control Group 1-5 contains the same type of additive B as the electrolyte of Experimental Group 1-1, but the electrolyte of Control Group 1-5 does not contain additive A. The test results of the control group 1-4 electrolyte and the control group 1-5 electrolyte and the lithium-ion batteries using these two electrolytes in this test example are compared. Under the same addition amount, the control group 1-4 electrolyte containing additive A and the lithium-ion batteries using it perform better than similar test objects in various performance tests. This shows that when applied separately, additive A can improve the performance of the electrolyte and the lithium-ion battery using it more effectively compared with additive B. However, compared with the control group 1-4, the experimental group 1-1 is equivalent to using additive B to partially replace additive A in the process of preparing the electrolyte. From the test results, the performance test results of the experimental group 1-1 electrolyte and the lithium-ion battery using it are better than those of similar test objects in this test example. This shows that when additives A and additives B are used together, they can synergize and better improve the comprehensive performance of the electrolyte and the lithium-ion battery used.
[0110] In addition to experimental group 1 experimental group 1-1, taking other experimental groups of Example 1 as controls, and setting comparative experiments with reference to the variable settings of experimental group 1-1, control group 1-4, and control group 1-5, performance difference performance consistent with the test results of this test example can also be obtained.
[0111] Table 4. Test result statistics of test case 2
[0112]
[0113]
[0114] Example 3
[0115] In this embodiment, based on the test results of Test Example 1 and Test Example 2, the preferred ratio of additive A and additive B in the electrolyte formula is further explored. According to the mass percentage of the components, the electrolyte formula used in this embodiment is as follows: the total amount of additive A and additive B is 0.7%, VC 0.2%, LiODFP 0.5%, PST 1%, lithium hexafluorophosphate (LiPF6) 15%, and the balance is an organic solvent component. In this embodiment, with the ratio of additive A and additive B as a variable, experimental group 3-1, experimental group 3-2, experimental group 3-3 and experimental group 3-4 are set with reference to experimental group 1-1 of Example 1. In the above experimental groups, the additive A used is triazine compound I, and the additive B used is triazole compound I. Table 5 shows the mass percentage and mass ratio of additive A and additive B in the electrolyte formula used in the above experimental groups. For the convenience of comparison, Table 5 also shows the content of additive A and additive B in the electrolyte formula used in experimental group 1-1 of Example 1.
[0116] Table 5. Variable settings between the electrolyte formulas used in each experimental group in Example 3
[0117] Group Additive A percentage Additive B ratio Additive A: Additive B (mass ratio) Experimental group 1-1 0.3% 0.4% 0.75:0.1 Experimental Group 3-1 0.23% 0.47% 0.5:1 Experimental group 3-2 0.31% 0.39% 0.8:1 Experimental group 3-3 0.16% 0.54% 0.3:1 Experimental Group 3-4 0.35% 0.35% 1:1
[0118] Experimental Group 3-1, Experimental Group 3-2, Experimental Group 3-3, and Experimental Group 3-4 prepared materials according to their respective electrolyte formula compositions, and then prepared the electrolyte in the manner used in Experimental Group 1-1 of Example 1.
[0119] Preparation Example 3
[0120] The electrolyte prepared in Example 3 is used to prepare the lithium-ion battery in this preparation example.
[0121] The method for preparing the lithium ion battery in this preparation example is consistent with the method for preparing the lithium ion battery in Preparation Example 1.
[0122] Test Example 3
[0123] The test item carried out in this test case is the cycle performance test of lithium ions.
[0124] 1. Test subjects
[0125] The lithium ion battery prepared in Preparation Example 3 was used as a test object.
[0126] 2. Test Method
[0127] The method used in this test example to perform cycle performance testing on lithium-ion batteries is consistent with the lithium-ion battery cycle performance testing method used in Test Example 1.
[0128] 3. Test results
[0129] The test results of this test example are shown in Table 6. For the sake of comparison, Table 6 also shows the test results of the lithium-ion battery prepared using the electrolyte of Experimental Group 1-1 of Example 1 in Test Example 1.
[0130] The test results of this test case show that among the test objects of this test case, experimental group 1-1, experimental group 3-1, and experimental group 3-2 provide better cycle performance of lithium-ion batteries. In the electrolyte formula used by the test object, when the ratio of additive A and additive B in the formula satisfies the mass of additive A: the mass of additive B = 0.5-0.8, the stability of the positive electrode CEI film and the negative electrode SEI film of the lithium-ion battery can be further improved, thereby improving the working stability of the lithium-ion battery.
[0131] In addition to the case where triazine compounds are used as additive A and triazole compounds are used as additive B, when other triazine compounds shown in Table 1 are used as additive A and other triazole compounds shown in Table 2 are used as additive B, and different combinations of additive A / additive B are used to prepare the electrolyte, it is met that when the mass of additive A: the mass of additive B = 0.5 to 0.8, the cycle performance of the lithium-ion battery is better.
[0132] Table 6. Statistics of lithium-ion battery cycle performance test results of test example 3
[0133]
[0134]
[0135] Example 4
[0136] In this embodiment, the electrolyte formula used in the experimental group 1-1 of embodiment 1 is used as a basis, and the sulfur-containing additives in the electrolyte formula are used as variables to set experimental groups 4-1, 4-2, and 4-3.
[0137] Experimental group 4-1: DTD was used to replace PST in the electrolyte formula of experimental group 1-1 in equal amounts, and the electrolyte formula obtained was used as the electrolyte formula of experimental group 4-1.
[0138] Experimental group 4-2: PS was used to replace PST in the electrolyte formula of experimental group 1-1 in equal mass, and the electrolyte formula obtained was used as the electrolyte formula of experimental group 4-2.
[0139] Experimental group 4-3: The organic solvent component in the electrolyte formulation of experimental group 1-1 was used to replace the PST in the electrolyte formulation of experimental group 1-1 in equal mass, and the electrolyte formulation obtained was used as the electrolyte formulation of experimental group 4-3.
[0140] Experimental Group 4-1, Experimental Group 4-2, and Experimental Group 4-3 prepared materials according to their respective electrolyte formula compositions, and then prepared the electrolyte in the manner used in Example 1 for preparing the electrolyte of Experimental Group 1-1.
[0141] Preparation Example 4
[0142] The electrolyte prepared in Example 4 is used to prepare the lithium-ion battery in this preparation example.
[0143] The method for preparing the lithium ion battery in this preparation example is consistent with the method for preparing the lithium ion battery in Preparation Example 1.
[0144] Test Example 4
[0145] 1. Cycle performance test of lithium-ion batteries
[0146] (1) Test object
[0147] The lithium ion battery prepared in Preparation Example 4 was used as a test object.
[0148] (2) Test method
[0149] The method used in this test example to perform cycle performance testing on lithium-ion batteries is consistent with the lithium-ion battery cycle performance testing method used in Test Example 1.
[0150] 2. High temperature storage performance test of lithium-ion batteries
[0151] (1) Test object
[0152] The lithium ion battery prepared in Preparation Example 4 was used as a test object.
[0153] (2) Test method
[0154] The method used in this test example to test the high temperature storage performance of lithium-ion batteries is consistent with the lithium-ion battery cycle performance test method used in Test Example 1.
[0155] 3. Test results
[0156] The test results of this test example are shown in Table 7. For the sake of comparison, Table 7 also shows the test results of the lithium-ion batteries prepared using the electrolyte of Experimental Group 1-1 of Example 1 in Test Example 1. The electrolytes prepared in Experimental Group 1-1 of Example 1, Experimental Group 4-1 of Example 4, and Experimental Group 4-2 of Example 4 respectively contain sulfur-containing additives, while the electrolyte prepared in Experimental Group 4-3 of Example 4 does not contain sulfur-containing additives. The test results of this test example show that the lithium-ion batteries using the electrolyte of Experimental Group 4-3 of Example 4, the electrolyte of Experimental Group 4-1 of Example 4, and the electrolyte of Experimental Group 4-2 of Example 4 respectively reach basically equivalent levels in various product performance tests. Compared with the above-mentioned lithium-ion batteries, the lithium-ion batteries using the electrolyte of Experimental Group 1-1 of Example 1 show certain advantages in various product performances measured in this test example. This shows that for the electrolyte system containing additives A and additives B, not any sulfur-containing additive can effectively improve the product performance of lithium-ion batteries using these electrolytes. However, based on the combination of additives A and additives B in the electrolyte, further using PST as a sulfur-containing additive can effectively improve the product performance of lithium-ion batteries using these electrolytes, especially, can effectively improve the high temperature performance of lithium-ion batteries.
[0157] Table 7. Test result statistics of test case 4
[0158]
[0159] The above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit the protection scope of the present invention. Although the present invention is described in detail with reference to the above embodiments, ordinary technicians in the relevant field should understand that the technical solutions of the present invention can be modified or equivalently replaced, but these modifications or replacements are all within the protection scope of the present invention.
Claims
1. An electrolyte, characterized in that: It includes additive A and additive B; the general structural formula of additive A is Wherein, at least one of R1, R2 and R3 is an alkeneoxy group; the general structural formula of the additive B is Wherein, R4 is a C1-C4 alkyl group.
2. The electrolyte according to claim 1, characterized in that The additive A is 3. The electrolyte according to claim 1, characterized in that: The general structural formula of the additive B is Wherein, R5 and R6 are independently selected from hydrogen, C1-C10 straight chain or branched alkyl or alkoxy, C1-C10 halogenated or unsubstituted straight chain or branched alkyl or alkoxy.
4. The electrolyte according to claim 1, characterized in that: The molar mass of the additive A is 190-300, the molar mass of the additive B is 100-180, and in the electrolyte, the mass ratio of the additive A to the additive B satisfies the mass of the additive A: the mass of the additive B = 0.5-0.8:
1.
5. The electrolyte according to claim 4, characterized in that: The sum of the masses of the additive A and the additive B accounts for 0.6 wt.% to 2 wt.% of the mass of the electrolyte.
6. The electrolyte according to any one of claims 1 to 5, characterized in that: The electrolyte further comprises at least one of a sulfur-containing additive, a carbonate additive, and a lithium salt additive; The sulfur-containing additive includes at least one of vinyl sulfate, 1,3-propane sultone, and 1,3-propylene sultone; The carbonate additive includes vinylene carbonate; The lithium salt additive includes at least one of lithium bis(fluorosulfonyl)imide, lithium difluorophosphate, lithium bis(oxalatoborate), and lithium difluorobis(oxalatophosphate).
7. The electrolyte according to claim 6, characterized in that: The sulfur-containing additive includes 1,3-propylene sultone, and in the electrolyte, the mass of the additive A:1,3-propylene sultone=0.3-1:0.5-2.
8. The electrolyte according to any one of claims 1 to 5, characterized in that: The electrolyte includes an organic solvent component, the mass of which accounts for 80wt.% to 90wt.% of the mass percentage of the electrolyte. The organic solvent component includes cyclic carbonate, chain carbonate and chain carboxylic acid ester. Calculated by mass ratio, the cyclic carbonate: the chain carbonate: the chain carboxylic acid ester = 10 to 25: 50 to 80: 5 to 20.
9. The electrolyte according to claim 8, characterized in that: The cyclic carbonate includes fluoroethylene carbonate and ethylene carbonate, the chain carbonate includes diethyl carbonate, and the chain carboxylic acid ester includes ethyl difluoroacetate.
10. A lithium ion battery, characterized in that: The lithium-ion battery comprises the electrolyte according to any one of claims 1 to 9.
Citation Information
Patent Citations
High-voltage lithium ion battery electrolyte film-forming additive, electrolyte and battery thereof
CN111900477A
Lithium ion battery electrolyte and lithium ion battery
CN114792842A
Electrolyte additive, electrolyte for lithium ion battery and lithium ion battery
CN117613389A
Electrolyte additive, non-aqueous electrolyte and lithium ion battery
CN117810539A
Electrolyte for nonaqueous secondary battery, nonaqueous secondary battery, and additive for electrolyte
JP2014127354A